High-density genetic map construction and identification of loci controlling flower-type traits in Chrysanthemum (Chrysanthemum × morifolium Ramat.). (1st July 2020) - Song, Xuebin; Xu, Yuhui; Gao, Kang; Fan, Guangxun; Zhang, Fan; Deng, Chengyan; Dai, Silan; Huang, He; Xin, Huaigen; Li, Yingying
Abstract: Flower type is an important and extremely complicated trait of chrysanthemum. The corolla tube merged degree (CTMD) and the relative number of ray florets (RNRF) are the two key factors affecting chrysanthemum flower type. However, few reports have clarified the inheritance of these two complex traits, which limits directed breeding for flower-type improvement. In this study, 305 F1 hybrids were obtained from two parents with obvious differences in CTMD and RNRF performance. Using specific-locus amplified fragment sequencing (SLAF-seq) technology, we constructed a high-density genetic linkage map with an average map distance of 0.76 cM. Three major QTLs controlling CTMD and four major QTLs underlying RNRF were repeatedly detected in the 2 years. Moreover, the synteny between the genetic map and other Compositae species was investigated, and weak collinearity was observed. In QTL regions with a high degree of genomic collinearity, eight annotated genes were probed in the Helianthus annuus L. and Lactuca sativa L. var. ramosa Hort. genomes. Furthermore, 20 and 11 unigenes were identified via BLAST searches between the SNP markers of the QTL regions and the C. vestitum and C. lavandulifolium transcriptomes, respectively. These results lay a foundation for molecular marker-assisted breeding and candidate gene exploration in chrysanthemum without a reference assembly.